A diversity-based strategy for asteroid tour design - Grabowski, Jan; Bellome, Andrea; Felicetti, Leonard (Elsevier, 2026)
The design of multi-target tours among the celestial bodies of the Solar System is one of the key drivers for scientific return in space exploration missions. Such missions could bring valuable insights into the evolution of our Solar System and the available resources by prospecting many targets with a single spacecraft. The generation of a sequence of encountered bodies is a combinatorial optimization problem that can be addressed with heuristic search algorithms. However, solving the optimization problem does not consider the diversity of the body population and heuristic search techniques often produce tours with the same encountered bodies. In this paper, a new search strategy based on the diversity of visited bodies is described. An asteroid tour diversity score is defined to serve as a metric for a new search strategy in the combinatorial optimization problem. The standard Beam Search algorithm is compared to diversity-based optimization for the generation of asteroid tours in the Main Asteroid Belt and Near-Earth Asteroid populations. Unlike Beam Search, the proposed diversity-based strategy does not generate duplicate sequences and facilitates the encounter of more asteroids at higher eccentricities and inclinations, at the cost of higher Δ v . A hybrid search strategy is shown to find better balance between asteroid tour diversity and Δ v cost. These study cases illustrate the performance of diversity-based search for the preliminary mission design of future asteroid tour missions.
Keywords: 51 Physical Sciences; Aerospace & Aeronautics; 5101 Astronomical sciences; 5109 Space sciences; Trajectory design; Asteroid tours; Combinatorial optimization; Maximum diversity problem